Rehabilitation of a Degraded Tropical Lowland Forest Using Three Indigenous Timber Species in Peninsular Malaysia - Bigcas, Evelyn Varquez (2003)
Seedlings of Azadirachta excelsa, Hopea odorata and Vitex pinnata were line- and gap- planted on a logged-over site in Pasoh Forest Reserve, Negeri Sembilan, Malaysia. After two and a half years of planting, H. odorata exhibited the h ighest average survival percentage of 97% in the large discontinuous gaps of 20m x 20m (G3 method), followed by V. pinnata 91%, and A. exce/sa 82%. In G4 (10m x 10m X 9/ha gaps), the survival percentage of H. odorata was 95%, followed by V. pinnata (89%) and A . excelsa ( 84%). In G2 (10m x 10m x 5/ha gaps), H. odorata showed 90% survival, followed by V. pinnata (71%) and A. excelsa (64%). In the line planting, H. odorata attained 93% survival, V. pinnata 84% and A. excelsa 75%. Relatively high survival percentages of the seedlings were due to the capacity of the seedlings to survive under situation typical of degraded lands. Moreover, relatively high light environment and high organic matter content may have also contributed to the low mortality. Mortality can be attributed to the activities of the wild boars that collected small twigs and seedlings as nest during breeding periods. The broken stems (reduced heights) that sometimes led to seedling death were mainly due to strong winds which are typical of Malaysia, the monkeys who play with and eat the top shoots, and the weeds who strangled and pulled the seedlings downwards. The relatively high survival rates are indicative of the species capacity to colonise and regenerate degraded lands.